2017
DOI: 10.1007/s10368-017-0375-5
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of Information and Communications Technology (ICT) and E-commerce on bilateral trade flows

Abstract: This study examines the impact of Internet and e-commerce adoption on bilateral trade flows using a panel of 21 developing-and least-developed countries and 30 OECD countries. Given the commitment of East African Community (EAC) to become the frontrunner in export-led economy across the African continent, special attention is dedicated to analyse the role of ICT and e-commerce on EAC's export performance. The empirical results indicate that better access to the modern ICT and adoption of e-commerce application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 31 publications
4
30
0
9
Order By: Relevance
“…Finally, study [61] considered the performance of companies operating exclusively on the Internet, called e-companies or dotcoms, analyzing factors that are intrinsic to the Web site, such as accessibility, web presence and utility.nets are playing a fundamental role in online business and customers are more concerned about the ethical issues of electronic commerce, including security, privacy, and trust. The vast majority of public sectors According to [205], in first world nations a better access to modern ICTs and the adoption of e-commerce applications stimulate bilateral commercial flows at various levels. The study points out efficient use of ICTs equipped with high speed Internet and safe servers as a crucial milestone to unblock e-commerce potential in developing countries.…”
mentioning
confidence: 99%
“…Finally, study [61] considered the performance of companies operating exclusively on the Internet, called e-companies or dotcoms, analyzing factors that are intrinsic to the Web site, such as accessibility, web presence and utility.nets are playing a fundamental role in online business and customers are more concerned about the ethical issues of electronic commerce, including security, privacy, and trust. The vast majority of public sectors According to [205], in first world nations a better access to modern ICTs and the adoption of e-commerce applications stimulate bilateral commercial flows at various levels. The study points out efficient use of ICTs equipped with high speed Internet and safe servers as a crucial milestone to unblock e-commerce potential in developing countries.…”
mentioning
confidence: 99%
“…Most recent researches only confirm the previous results. One of the studies that included 51 countries, 30 OECD member countries and 21 medium and low-income countries indicated that better access to modern information and communications technologies and e-commerce applications boost bilateral trade flows among different groups of countries (Xing, 2017). Results implied that the Internet penetration and adoption, number of broadband subscriptions and secured servers greatly affected the trade among the observed groups, the so-called Southern and Northern economies.…”
Section: The Impact Of Information and Communications Technologies Onmentioning
confidence: 99%
“…In recent years, e-government has been one of the most critical technologies in ICT. Using of IT tools for some people is ordinary in their daily lives, while others still choose traditional ways to use (Greenland, 2019;Xing, 2018). There is no particular e-government definition, and most definitions emphasize on better delivery of government services to beneficiaries by using technology.…”
Section: Introductionmentioning
confidence: 99%